David's spiritual walls and conceptual blending in Psalm 51. (June 2019) - Ross, William A
Owing to the apparent topical disjunction of the final two verses of Psalm 51, many commentators consider them a later addition, particularly given the attitude toward sacrifice and the reference to Jerusalem's walls. By taking a cognitive linguistic approach, particularly applying Fauconnier and Turner's theory of conceptual blending, this article demonstrates the unity of the Psalm as a discourse unit. Additionally, this article builds upon literary structural analyses of others to suggest the complementarity of the cognitive linguistic and literary approaches. This analysis of Psalm 51 as a whole demonstrates that, not only do vv. 20–21 cohere with the entire psalm, they do so by interacting with vv. 18–19 to build meaning from a single conceptual blend network, one that depends upon the conceptual structures prompted by the narrative setting throughout the discourse. On this reading, David himself is Zion/Jerusalem whose damaged spiritual walls require restoration by Yhwh as a builder.